The organizational tension between static and dynamic efficiency - Ghemawat, Pankaj; Ricart, Joan E. (Strategic Management Journal, 1993)
Efficiency has been defined in at least two different ways: in terms of the refinement of existing products, processes or capabilities (static efficiency) or the development of new ones (dynamic efficiency). This paper analyzes the organizational trade-off between these two forms of efficiency. It shows that there is a tendency towards extremes, and that the irreversibility of efficiency orientations tends to tip the balance to be struck between static and dynamic efficiency toward the latter. The paper also advances hypotheses about the industry, business and corporate factors that mediate between the choice of a particular efficiency orientation and organizational performance.